Unveiling the Challenges in Topical Corticosteroid Usage: Insights from Pharmacists and Physicians - Kandoth, Sreeraj; Rompicherla, Narayana Charyulu; Shenoy, Sarath Chandran Chadrashekar; Mateti, Uday Venkat; Joel, Juno Jerold; Mohanan, Sarin Shyamala (International Journal of Pharmaceutical Investigation, 2026)
Background Topical Corticosteroids (TCs) are widely prescribed for managing dermatological conditions due to their efficacy in reducing inflammation and related symptoms. However, misuse, suboptimal prescribing practices, and insufficient patient education contribute to significant challenges in ensuring safe and effective use. Aim and Objectives The objective of the study was to investigate the knowledge, practices, and perceptions of community pharmacists and physicians regarding TCs usage. Material and Methods A qualitative approach Focus Group Discussions (FGDs) was conducted in Kannur District, Kerala (India) regarding TCs usage. Two FGDs were conducted separately with physicians and pharmacists and the discussions were continued until no new findings emerged. All the sessions were recorded, and transcribed. Results and Discussion The FGDs highlighted that while physicians possess substantial knowledge of TC classifications and appropriate applications, gaps exist in patient communication and regulatory enforcement. Pharmacists often face pressures to dispense TCs without prescriptions due to economic constraints and market competition. Both groups reported frequent cases of misuse by patients, including improper use and application of leftover prescriptions. Adverse drug reactions, such as skin atrophy, telangiectasia, and tachyphylaxis, were reported due to long-term TC misuse. Conclusion Key themes emerging from the discussions include the need for enhanced education and training for healthcare providers, stricter regulatory oversight, and improved patient education. The study recommends implementing continuing medical education programs focused on TCs, promoting patient awareness campaigns, and enforcing prescription-only sales through stricter regulation.
Keywords: Adverse drug reaction; Dermatology; Focus group discussions; Topical corticosteroids